COMPARISON OF DEXMEDETOMIDINE AND LIGNOCAINE ON ATTENUATION OF PRESSOR RESPONSES DURING TRACHEAL EXTUBATION - PRAJAPATI, JAYSHRI; PATEL, MAITRI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to evaluate and observe the effects of single bolus intravenous dose of Dexmedetomidine with Lignocaine on the hemodynamic changes and pressor responses during tracheal extubation in patients undergoing elective surgery under general anesthesia. Methods: This prospective and observational study was conducted in anesthesia department of tertiary care teaching hospital of Gujarat. Group A received single bolus dose of Dexmedetomidine 0.5μg/kg IV (diluted in 10 ml normal saline) over 10 min after completion of surgery and Group B received single bolus dose of Lignocaine 1.5 mg/kg IV (diluted in 10ml normal saline) over 60 s before extubation. Hemodynamic parameters were recorded before administration of drug (baseline), at extubation and post-extubation in both groups. Extubation quality was evaluated using a five-point scale. Complications were also compared in both the groups. Results: Heart rate was 89.67±7.19 beats/minute in Group A at the time of extubation and in Group B, it was 115±6.88 beats/min which was found highly significant (p<0.0001). Mean systolic blood pressure (SBP) in Group A was 130.55±9.4 mmHg at the time of extubation and in Group B, it was 142±9.58 mmHg which was highly significant (p<0.0001). Mean diastolic blood pressure (DBP) in Group A was 85.76±3.26 mmHg at the time of extubation and in Group B, it was 99.1±2.86 mmHg which was highly significant (p<0.0001). Statistical significant difference was also observed between both the groups for heart rate, SBP, and DBP from extubation to 60 min post-extubation (p<0.05). Conclusions: This study concluded that single bolus dose of intravenous Dexmedetomidine was more effective in maintaining hemodynamic stability and attenuating airway reflex responses as compared to lignocaine.